Advances in application of photon-counting CT for pancreatic imaging - HUANG Ruikun, YANG Yanzhao, CHAI Weimin (Zhenduanxue lilun yu shijian, 2025)
Photon-counting computed tomography (PCCT) is an advanced CT imaging technology based on novel photon-counting detectors. Compared to traditional energy-integrating detector CT (EID-CT), PCCT demonstrates significant advantages in radiation dose utilization efficiency, image spatial resolution, and spectral resolution, and is expected to revolutionize imaging diagnostic paradigms for pancreatic diseases. This study systematically reviews the latest research advances in PCCT for pancreatic imaging, with a focus on its clinical application value in displaying fine pancreatic anatomical structures, visualizing the pancreas, surrounding vascular networks, and pancreaticobiliary systems, evaluating benign and malignant lesions, and quantitatively assessing tumor heterogeneity. The core technical principles of PCCT include physical characteristics such as high photon-flux processing by photon-counting detectors, K-edge imaging, and multi-energy threshold data acquisition modes. On this basis, this study summarizes optimization strategies for pancreatic imaging, including scan parameter settings and the clinical application of multimodal post-processing techniques. PCCT can effectively reduce radiation dose while overcoming the spatial resolution bottleneck, thereby improving the detection rate of cystic lesions. The low-energy monoenergetic reconstruction mode of PCCT can enhance the contrast of solid tumors and optimize the visualization of branching and tumor-feeding vessels. By integrating representative clinical studies and preliminary validation trials in recent years, this study further analyzes key challenges and corresponding strategies during the clinical translation of PCCT. Additionally, it explores the future directions of this technology in the precise diagnosis of pancreatic diseases, personalized treatment decision support, and the development of AI-big data models, aiming to provide a theoretical foundation and practical reference for promoting PCCT applications in the field of pancreatic imaging.